Highly divergent regions in the complete plastome sequences of Aquilaria are suitable for DNA barcoding applications including identifying species origin of agarwood products - Hishamuddin, Muhammad Syahmi; Shiou, Yih Lee; Syazwan, Samsuddin Ahmad; Ramlee, Shairul Izan; Lamasudin, Dhilia Udie; Mohamed, Rozi (Springer, 2023)
Members of Aquilaria Lam. (Thymelaeaceae) are evergreen trees that are widely distributed in the Indomalesia region. Aquilaria is highly prized for its unique scented resin, agarwood, which is often the subject of unlawful trade activities. Survival of the tree is heavily threatened by destructive harvesting and agarwood poaching, leading to its protection under the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Unfortunately, an efficient species identification method, which is crucial to aid in the conservation efforts of Aquilaria is lacking. Here, we described our search for a suitable specific DNA barcode for Aquilaria species using eight complete plastome sequences. We identified five highly variable regions (HVR) (matK-rps16, ndhF-rpl32, psbJ-petA, trnD, and trnT-trnL) in the plastomes. These regions were further analyzed using the neighbor-joining (NJ) method to assess their ability at discriminating the eight species. Coupled with in silico primer design, two potential barcoding regions, psbJ-petA and trnT-trnL, were identified. Their strengths in species delimitation were evaluated individually and in combination, via DNA barcoding analysis. Our findings showed that the combined dataset, psbJ-petA + trnT-trnL, effectively resolved members of the genus Aquilaria by clustering all species into their respective clades. In addition, we demonstrated that the newly proposed DNA barcode was capable at identifying the species of origin of six commercial agarwood samples that were included as unknown samples. Such achievement offers a new technical advancement, useful in the combat against illicit agarwood trades and in assisting the conservation of these valuable species in natural populations.